Revision of the portuguese catalog of tsunamis - Baptista, Maria Ana Carvalho Viana (2009)
Catastrophic tsunamis are described in historical sources for all regions around the Gulf of Cadiz, at least since 60 BC. Most of the known events are associated with moderate to large earthquakes and among them the better studied is 1 November 1755. We present here a review of the events which effects, on the coasts of the Portuguese mainland and Madeira Island, are well described in historical documents or have been measured by tide gauges since the installation of these instruments. For a few we include new relevant information for the assessment of the tsunami generation or effects, and we discard events that are included in existing compilations but are not supported by quality historical sources or instrumental records. We quote the most relevant quantitative descriptions of tsunami effects on the Portuguese coast, including in all pertinent cases a critical review of the coeval sources, to establish a homogenous event list. When available, instrumental information is presented. We complement all this information with a summary of the conclusions established by paleo-tsunami research.